2021
DOI: 10.3390/ijms22052424
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated CD38 Expression on Peripheral Blood Immune Cell Subsets in SLE

Abstract: Given its uniformly high expression on plasma cells, CD38 has been considered as a therapeutic target in patients with systemic lupus erythematosus (SLE). Herein, we investigate the distribution of CD38 expression by peripheral blood leukocyte lineages to evaluate the potential therapeutic effect of CD38-targeting antibodies on these immune cell subsets and to delineate the use of CD38 as a biomarker in SLE. We analyzed the expression of CD38 on peripheral blood leukocyte subsets by flow and mass cytometry in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
4
24
0
Order By: Relevance
“…In fact, a trial in patients with SLE who were resistant to anti-TNFα therapy found that targeting CD38 with daratumumab, which depletes CD38 expressing cells, ameliorates disease 58 . Our data show that multiple circulating and cutaneous cell types in patients with HS upregulate CD38, which is involved in multiple mechanisms that enhance inflammation 27,28,30,34,35,59 . Our IHC and bioinformatic analysis also found a robust increase of CD38 in lesional, but not perilesional HS skin.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, a trial in patients with SLE who were resistant to anti-TNFα therapy found that targeting CD38 with daratumumab, which depletes CD38 expressing cells, ameliorates disease 58 . Our data show that multiple circulating and cutaneous cell types in patients with HS upregulate CD38, which is involved in multiple mechanisms that enhance inflammation 27,28,30,34,35,59 . Our IHC and bioinformatic analysis also found a robust increase of CD38 in lesional, but not perilesional HS skin.…”
Section: Discussionmentioning
confidence: 74%
“…In rheumatoid arthritis (RA), the inhibition of CD38 activation by anti-CD38 monoclonal antibody has been effective to reduce RA symptoms and disease progression. In systemic lupus erythematosus (SLE) patients, the upregulation of CD38 expression in marginal zone-like IgD + CD27 + B cells has been reported ( 72 ), and the depletion of CD38 in pristane-induced lupus mouse model significantly improve the symptom ( 73 ). Thus, CD38 upregulation in B cells seems to be related to inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…The Change of CD38inchondrocytesis Associated with OA Development CD38 has been proven to be correlated with autoimmune diseases like Systemic Lupus Erythematosus (SLE), systemic sclerosis (SSc) and rheumatoid arthritis (RA) [23][24][25] . However, whether or not CD38 is involved in the progression of OA is still unclear.…”
Section: Discussionmentioning
confidence: 99%